Antecedents of Patient Experiential Satisfaction and Its Effect on Revisit Intention - Merry, Merry; Wuisan, Dewi Sri Surya; Baguna, Khakan (Universitas Islam Kadiri, 2025)
Introduction/Main Objectives: This paper examines declining patient visits in private clinics in Central Kalimantan, focusing on XYZ Clinic, which relies solely on out-of-pocket payments. Despite surviving the COVID-19 crisis, the clinic saw a sharp decrease in visits in 2023, highlighting the need to understand patient loyalty drivers. Background Problems: The main issue addressed in this study is the sustainability of private healthcare services, specifically examining the influence of price fairness, Clinic Image, and communication on patients’ revisit intention, with experiential satisfaction acting as a mediating factor. Novelty: This study integrates communication, price fairness, and Clinic Image in a single model with satisfaction as a mediator, an approach not widely explored in Indonesian private clinic contexts. Research Methods: A cross-sectional quantitative design was used. Data were gathered via structured questionnaires from 162 XYZ Clinic patients and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Advanced analytics were also performed. Finding/Results: Price fairness and communication significantly affect experiential satisfaction, with communication being the strongest factor. Both fairness and satisfaction influence revisit intention, while Clinic Image has no significant effect. Conclusion: The findings suggest that private clinics should focus on transparent communication and fair pricing to enhance patient loyalty, rather than relying solely on image-building strategies.